2013
DOI: 10.2139/ssrn.2245657
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Green: Behavioral Economics and Environmental Protection

Abstract: I. Beyond IncentivesSuppose that in a relevant community, there are two sources of energy, denominated "green" and "gray." Suppose that consistent with its name, "green" is better than gray on environmental grounds. Those who use green energy emit lower levels of greenhouse gases and also of conventional pollutants. Suppose that those who use gray energy save money. Which will consumers choose?The obvious response is that the answer will depend on the magnitude of the relevant differences. Suppose that green e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 1 publication
3
138
0
7
Order By: Relevance
“…Similarly, Lofgren and colleagues [35] found that default choice framing for carbon offsets did not influence offset purchases among experienced consumers (i.e., environmental economists), and concluded that experience in a given domain can attenuate the default effect. This aligns with work suggesting that some individuals may actually enjoy information gathering, weighing choice alternatives, and making a decision on their own ("market mavens") [36]. For instance, some smart home occupants perceive that automation is "dumbing down" their experience [3], and value the ability to make their own decisions about the functions of smart home technologies.…”
Section: Moderators Of the Default Effectsupporting
confidence: 67%
See 1 more Smart Citation
“…Similarly, Lofgren and colleagues [35] found that default choice framing for carbon offsets did not influence offset purchases among experienced consumers (i.e., environmental economists), and concluded that experience in a given domain can attenuate the default effect. This aligns with work suggesting that some individuals may actually enjoy information gathering, weighing choice alternatives, and making a decision on their own ("market mavens") [36]. For instance, some smart home occupants perceive that automation is "dumbing down" their experience [3], and value the ability to make their own decisions about the functions of smart home technologies.…”
Section: Moderators Of the Default Effectsupporting
confidence: 67%
“…Similar to the effect of experience, researchers argue that "insurmountable attitudes" [38] should attenuate the effect of a default [36]. However, experimental work has found that attitude strength only overrides the default effect among those with extremely strong attitudes (i.e., top 7%) and only for very specific attitudes (i.e., toward renewable energy vs. general environmental attitudes) [39].…”
Section: Moderators Of the Default Effectmentioning
confidence: 96%
“…This default saved than 7 million pages in one semester, or 620 trees (CAS 2011). Sunstein and Reisch (2013) provide several other examples of defaults in the context of green energy, paper savings and smart grids.…”
Section: Default Options and Related Schemesmentioning
confidence: 99%
“…At first sight, this point seems intuitive: After all, nudges are most effective in situations where individuals lack complete preferences -in that case, nudges interfere with processes of preference formation. In the limit, this interference may substitute the nudger's 55 See also Sunstein and Reisch (2014). 56 Attari et al (2009) found that subjects preferred soft to hard regulation (note, however, that 'soft regulation' included non-nudges such as monetary incentives, see ibid.).…”
Section: Do Nudges Compromise People's 'Autonomy'?mentioning
confidence: 99%